Dissolution feature differences of carbonate rock within hydro-fluctuation belt located in the Three Gorges Reservoir Area - Chen, Chiwei; Yang, Haiqing; Song, Kanglei; Liang, Dan; Zhang, Yuhan; Ni, Jianghua (Engineering geology, 2023)
The stability of geological environment in the Three Gorges Reservoir Area (TGRA) has experienced severe challenges due to the 30 m hydro-fluctuation belt (HFB). The vertical dissolution features vary with the mechanism of water and rock interaction. Although dissolution features have been adequately explained by physical and mechanical parameters, the characterization of chemical changes in dissolution is vital but frequently neglected information. For this purpose, the hyperspectral characteristics and mineralogical composition variation of rock HFB in different areas of the Triassic Daye Formation are tested to elucidate the dissolution behaviors. Then, the deterioration degree of dissolution is quantified by a multi-objective data integration based on Random Forest Regression (RFR) model. The spatial distribution of dissolution and the seasonal deterioration characteristics are identified depending on the spectral response of carbonate. Specifically, the dissolution degree is proportional to elevation, and inverse to the bedding angle at 0–40° in the investigated stratum. Combined with the hydrological characteristics of study area, the corresponding regional phenomena can be distinguished as reservoir water dominated, rainfall dominated, and coupled action. Affected by reservoir water and acid rainfall, the HFB may deteriorate most severely from January to April. In addition, the contribution of RFR model integrated spectral and geometric data to the deterioration evaluation of the HFB is discussed, which can effectively enhance the identification of rock mass boundary in a single spectral data model. Thus, these results are conducive to the rapid evaluation of regional geomorphological characteristics and the monitoring of geological disasters in the TGRA. •Dissolution of hydro-fluctuation belt is characterized by hyperspectral response.•Reservoir level and rainfall have different effects on carbonate rock dissolution.•Deterioration mechanism of rock with seasonal hydrological feature is revealed.•A rock deterioration evaluation model based on spectra and geometry is proposed.